Single‐leg drop landing movement strategies 6 months following first‐time acute lateral ankle sprain injury. Issue 6 (29th December 2014) - Doherty, C.; Bleakley, C.; Hertel, J.; Caulfield, B.; Ryan, J.; Delahunt, E.
Abstract : No research exists predicating a link between acute ankle sprain injury‐affiliated movement patterns and those of chronic ankle instability (CAI) populations. The aim of the current study was to perform a biomechanical analysis of participants, 6 months after they sustained a first‐time acute lateral ankle sprain (LAS) injury to establish this link. Fifty‐seven participants with a 6‐month history of first‐time LAS and 20 noninjured participants completed a single‐leg drop landing task on both limbs. Three‐dimensional kinematic (angular displacement) and sagittal plane kinetic (moment of force) data were acquired for the joints of the lower extremity, from 200 ms pre‐initial contact (IC) to 200 ms post‐IC. Individual joint stiffnesses and the peak magnitude of the vertical component of the ground reaction force (GRF) were also computed. LAS participants displayed increases in hip flexion and ankle inversion on their injured limb ( P  < 0.05); this coincided with a reduction in the net flexion‐extension moment at the hip joint, with an increase in its stiffness ( P  < 0.05). There was no difference in the magnitude of the peak vertical GRF for either limb compared with controls. These results demonstrate that altered movement strategies persist in participants, 6 months following acute LAS, which may precipitate the onset of CAI.